The tax terminology of the Short collection of Khan’s jarlyks issued to Rus’ Metropolitans - Maslova S.A. (Золотоордынское обозрение)
Research objectives: This study aims to determine the nature of payments made to the Golden Horde, as documented in the texts of the Short Collection of Khan’s jarlyks issued to Rus’ Metropolitans. Research materials: The research draws from various sources, including charters prepared by the orders of the Golden Horde and Yuan Empire rulers, charters of a spiritual and contractual nature from Rus’ princes, as well as Rus’ chronicles. Results and novelty of the research: This study proposes characteristics of the tax items found in Khan’s jarlyks and uncovers potential insertions within the label texts. It is demonstrated that the extensive list of duties present in the Khan’s charters was not originally a part of these documents. Many tax terms were intentionally added to the texts of the jarlyks during their translation into Russian. Some of these terms represented the Horde taxes that were actually collected from Russian lands, while others denoted payments recognized in Rus’, but not directed to the benefit of the Golden Horde. Furthermore, certain terms appear to be artificial tax designations.